Hydrogen production utilizing glycerol from renewable feedstocks-The case of Brazil - Souza, Antonio Carlos Caetano de [UNESP]; Silveira, Jose Luz [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Various reports concerning catalytic reaction of glycerol for hydrogen production is available. However, economic analyses of this activity are not found yet. The objective of this work is to evaluate the process of hydrogen production via steam reforming of glycerol obtained through transesterification process of bio-oils. The thermochemical process of steam reforming process was determined due to high efficiency, feasibility and lower cost of design, development, operation and maintenance. These bio-oils come from feedstocks largely encountered in Brazil such as soybean, palm, castor bean, peanut and cotton seed as also come from residues such as defective coffee, tallow beef, wastewater (scum) and others. Various findings were obtained such as potential of production of glycerol utilizing residues (considering available amounts in the Brazilian states) and some vegetable feedstocks (considering production of harvested feedstock per hectare). Subsequently, production of hydrogen via steam reforming of generated glycerol, and foreseen electricity production via fuel cells were also determined. An additional estimation was paid for production of H-BIO, an innovative fuel developed by PETROBRAS (Petroleo Brasileiro S.A.), where hydrogen and bio-fuel are utilized and generates propane as co-product. About this work, it was concluded that high amounts of hydrogen and electricity could be produced considering an enormous potential from each cited feedstock being an attractive alternative as distributed electricity source and as an additional source for some activities, inclusively those that produce their own feedstocks such as abattoirs (beef tallow), and wastewater treatment plants. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Hydrogen production; Glycerol; Transesterification; Vegetable feedstocks; Residues H-BIO